2010
DOI: 10.1111/j.1365-2672.2010.04718.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of vibrios in the haemolymph of the spider crab Maja brachydactyla

Abstract: Aims:  The aim of this study was to characterise and identify vibrios isolated from the haemolymph of apparently healthy adult spider crabs (Maja brachydactyla) wild‐caught in the Spanish localities of Galician coast and in the Canary Islands and also from captive animals held at IRTA’s facilities in the Ebro Delta of Catalonia, north‐west Spanish Mediterranean coast. Methods and Results:  A total of 277 bacterial isolates were obtained, and of these, 171 were characterised with rep‐PCR, resulting electrophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…were found in large numbers but only in one or two shrimp samples. Vibrios from the Orientalis clade and its close relatives have been found associated with aquatic animals such as in the hemolymph of spider crab Maja brachydactyla [18] and in the digestive tract of Chinese prawn Penaeus chinensis [65]. Many Vibrio species observed in this study have been associated with diseases in other organisms such as coral (V. coralliilyticus/V.…”
Section: Discussionmentioning
confidence: 94%
“…were found in large numbers but only in one or two shrimp samples. Vibrios from the Orientalis clade and its close relatives have been found associated with aquatic animals such as in the hemolymph of spider crab Maja brachydactyla [18] and in the digestive tract of Chinese prawn Penaeus chinensis [65]. Many Vibrio species observed in this study have been associated with diseases in other organisms such as coral (V. coralliilyticus/V.…”
Section: Discussionmentioning
confidence: 94%
“…Studies in crabs and shrimps have shown that haemolymph metabolites can be used as valuable biomarkers for assessing the physiological condition of wild and cultured animals (Durand, Devillers, Lallier & Regnault 2000;Frederich & Pörtner 2000;Palacios 2000;Sanchez, Pascual, Sánchez, Vargas-Albores, LeMoullac & Rosas 2000;Pascual, Gaxiola & Rosas 2005). In this sense, recent findings have suggested that bacterial populations found in the haemolymph of the apparent healthy spider crabs could be used as an indicator of the health status of captive animals (Gómez-Gil, Roque, Lacuesta & Rotllant 2010). In this sense, recent findings have suggested that bacterial populations found in the haemolymph of the apparent healthy spider crabs could be used as an indicator of the health status of captive animals (Gómez-Gil, Roque, Lacuesta & Rotllant 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tissues of healthy marine invertebrates usually harbor species-rich microbial communities (Prieur et al, 1990;Gomez-Gil et al, 1998;Romero et al, 2002;Gomez-Gil et al, 2010;King et al, 2012;Trabal et al, 2012;Wegner et al, 2013). This also applies to the hemolymph (Olafsen et al, 1993;Garnier et al, 2007, Wendling et al, 2014-the functional analog of blood in vertebrates (Bachere et al, 2004).…”
Section: Introductionmentioning
confidence: 99%